History and monumentalism of the Rejang Dewa dance in Bali, Indonesia - Widyastuti, Ida Ayu Gede Sasrani; Saptono,; Santosa, Hendra; Sutirtha, I Wayan (Humanities, Arts and Social Sciences Studies, 2025)
This study explores the evolutionary journey of the Rejang Dewa dance as a monumental dance of Bali. The objective is to elucidate the history of Rejang Dewa dance creation and identify important factors in its monumentalism process. A qualitative research model using a phenomenological approach was employed in this study. Data collection involved in-depth interviews with the dance and music creators of the Rejang Dewa dance, who served as informants, as well as an analysis of relevant audiovisual documents. We matched and analyzed the interview data interpretatively to produce a written draft, which was then validated by involving the informants. We arranged the research findings chronologically and systematically, based on the informants’ confirmatory feedback. The results indicate that three main factors support the monumentalism process of Rejang Dewa dance: (1) the influence of power and policy, (2) the role of academic institutions, and (3) the historical context and evolution of art. Movement and sacred art music serve as aesthetic sources contributing to the artistic richness of Rejang Dewa dance. This demonstrates the success of utilizing local resources to create distinctive art. The long journey of Rejang Dewa dance shows that it has passed through various important historical events that have shaped its characteristics and functions. Balinese Hindu communities in Indonesia commonly use this dance for both ritual and profane ceremonial purposes. These findings have implications for strengthening cultural identity through a deeper understanding of traditional art preservation.